2020
DOI: 10.1074/jbc.ra120.013988
|View full text |Cite
|
Sign up to set email alerts
|

15-Keto-PGE2 acts as a biased/partial agonist to terminate PGE2-evoked signaling

Abstract: Prostaglandin E2 (PGE2) is well-known as an endogenous pro-inflammatory prostanoid synthesized from arachidonic acid by the activation of cyclooxygenase-2. E type prostanoid (EP) receptors are cognates for PGE2 that have four main subtypes: EP1 to EP4. Of these, the EP2 and EP4 prostanoid receptors have been shown to couple to Gαs-protein and can activate adenylyl cyclase to form cAMP. Studies suggest that EP4 receptors are involved in colorectal homeostasis and cancer development, but further work is needed t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

7
22
0

Year Published

2020
2020
2023
2023

Publication Types

Select...
6

Relationship

2
4

Authors

Journals

citations
Cited by 10 publications
(29 citation statements)
references
References 28 publications
(27 reference statements)
7
22
0
Order By: Relevance
“…Cell culture and materials HEK-EP2 cells or HEK-EP4 cells [11] were cultured in Dulbecco's modified Eagle's medium (DMEM; Nacalai Tesque, Kyoto, Japan) containing 10% FBS (Thermo Fisher Scientific, Waltham, MA, USA), 250 μgÁmL −1 of geneticin (Phyto Technology Laboratories, Shawnee Mission, KA, USA), 200 μgÁmL −1 of hygromycin B (Enzo Life Science, Farmingdale, NY, USA), and 100 μgÁmL −1 of gentamicin (Life Technologies, Carlsbad, CA, USA) at 37 °C. PGE 2 was obtained from Cayman Chemical (Ann Arbor, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
See 1 more Smart Citation
“…Cell culture and materials HEK-EP2 cells or HEK-EP4 cells [11] were cultured in Dulbecco's modified Eagle's medium (DMEM; Nacalai Tesque, Kyoto, Japan) containing 10% FBS (Thermo Fisher Scientific, Waltham, MA, USA), 250 μgÁmL −1 of geneticin (Phyto Technology Laboratories, Shawnee Mission, KA, USA), 200 μgÁmL −1 of hygromycin B (Enzo Life Science, Farmingdale, NY, USA), and 100 μgÁmL −1 of gentamicin (Life Technologies, Carlsbad, CA, USA) at 37 °C. PGE 2 was obtained from Cayman Chemical (Ann Arbor, MI, USA).…”
Section: Methodsmentioning
confidence: 99%
“…Recently, 15‐keto‐PGE 2 , a metabolite of PGE 2 , was reported to act as a switch for cellular signaling to the EP2 receptor‐mediated pathway from the EP4 receptor‐mediated pathway [ 11 ]. Thus, PGE 2 ‐initiated EP4 receptor‐mediated signaling may be terminated by the subsequent 15‐keto‐PGE 2 ‐adopted EP2 receptor‐mediated signaling if both receptors are expressed on nearby tissues/cells.…”
mentioning
confidence: 99%
“…On the one hand, very complex structures that are phlorotannins, isolated from Eisenia bicyclis and Ecklonia cava, behave as agonists of dopamine receptors and may contribute to reduce the toxic effect of a compound, 1-methyl-4-phenylpyridinium (MPP + ), used for the development of Parkinson's disease animal models [17,21]. On the other hand, Gracilaria verrucose produces a high number of prostaglandins (PGs) such as PGA 2 , PGE 2 , PGF 2 , and 15-keto-PGE 2 , (some of which have the same chemical structures as mammalian PGs) that are able to interact with prostanoid receptors [18,22,23].…”
Section: Compounds From Protoctists (Algae)mentioning
confidence: 99%
“…We recently reported that a metabolite of PGE 2 , 15‐keto‐PGE 2 may have an additional role as a biased/partial agonist to take over the actions of PGE 2 to gradually terminate reactions through the EP2 and EP4 receptors. [ 39 ] Although 15‐keto‐PGE 2 is regarded as an inactive metabolite of PGE 2 , it functions as a “switched agonist” for cellular signaling from the EP4 receptor‐mediated pathway to the EP2 receptor‐mediated pathway, thereby restoring/terminating inflammatory reaction and/or maintaining homeostasis, such as in colorectal tissues/cells functions. [ 39 ] Endogenous PGD 2 and/or PGE 2 may function as biased ligands to exert opposing functions through the same receptors.…”
Section: Introductionmentioning
confidence: 99%
“…[ 39 ] Although 15‐keto‐PGE 2 is regarded as an inactive metabolite of PGE 2 , it functions as a “switched agonist” for cellular signaling from the EP4 receptor‐mediated pathway to the EP2 receptor‐mediated pathway, thereby restoring/terminating inflammatory reaction and/or maintaining homeostasis, such as in colorectal tissues/cells functions. [ 39 ] Endogenous PGD 2 and/or PGE 2 may function as biased ligands to exert opposing functions through the same receptors. Since the amount of endogenous prostanoids, including their metabolites, is vast, if these biased mechanisms are elucidated in more detail and properly utilized, prostanoids have potential as useful endogenous biased ligands and/or as leading compounds for the development of novel therapeutics in the future.…”
Section: Introductionmentioning
confidence: 99%